The Influence of Human Capital and Work Discipline on the Performance of Employees of the National Narcotics Agency of North Sumatra Province - Radhika Narwastu; Hilma Harmen (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to analyze the influence of Human Capital and Work Discipline on Employee Performance at the National Narcotics Board of North Sumatra Province (BNNP Sumut) for the 2019–2024 period. The method employed is explanatory quantitative, with a sample of 54 respondents (organic civil servants). Data were collected through Likert scale questionnaires and analyzed using multiple linear regression via SPSS. The t-test results indicate that Human Capital has a positive and significant effect on performance (t-count 3.991 > 1.984; sig 0.000), while Work Discipline has a positive but non-significant effect. Simultaneously (F-test), both variables significantly influence performance (F-count 10.798 > 3.18; sig 0.000). An R-Square value of 0.297 indicates that Human Capital and Work Discipline contribute 29.7% to employee performance, while the remaining 70.3% is influenced by other factors outside this study.